SPIRITUALITAS IGNASIAN MEMANDANG PENDERITAAN - Susanto, Gabriel Abdi (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2024)
Ignatian spirituality places particular emphasis on the meaning of suffering as a means of drawing closer to Christ. In the teachings of Ignatius Loyola, suffering is not seen as an end in itself, but as a path to respond to Christ’s call with fidelity. Through meditations such as The Call of the King and The Meditation on Two Standards, retreat participants are invited to understand suffering as an integral part of a life centered on God, where suffering becomes a way to experience a deeper connection with the Christ who suffered. In this context, suffering is not sought for its own sake, but as an expression of detachment and willingness to follow God’s will in all circumstances. By accepting suffering, one experiences the liberating love of God, leading to inner transformation and a deeper understanding of faith. Ignatian spirituality thus places suffering as an essential part of the spiritual journey, guiding the individual to a more meaningful life in unity with Christ.